Effectiveness of Mathematics Learning using the Google Sites Application at Junior High School - Fauziyah, Nur; Martiningsih, Raden Roro (Universitas Muhammadiyah Mataram, 2025)
Building innovative learning can be achieved by utilizing the Google Sites application in learning the topic of value comparison in grade VII of junior high school. The purpose of this study was to determine the effectiveness of using Google Sites in value comparison learning at SMP Muhammadiyah 1 Surabaya. This study used an experimental research design to compare the mathematics learning achievements of grade VII students at SMP Muhammadiyah 1 Surabaya who utilized Google Sites and those who did not. The treatment provided was the use of Google Sites in value comparison learning, referred to as the experimental class, consisting of 24 students. Meanwhile, learning in the class that did not use Google Sites was called the control class, consisting of 22 students. Both the experimental and control classes had the same mathematical abilities, based on the results of the homogeneity test using the summative scores from the previous semester. The research instrument was substantively validated by experts. Through Google Sites, students can access content such as texts, instructional videos, and quizzes organized on a site that is easily accessible to them anytime and anywhere. Google Sites allows students to learn independently, offering visual explanations of math concepts and providing immediate feedback through online quizzes. The results of this study showed that the average difference in the learning achievement of value comparison between students who utilized Google Sites was 8.125, while the group of students who did not utilize it was 6.00. The results of the t-test showed a significance value of 0.007, with a significance level of 0.05, indicating a significant difference in the learning achievement of value comparison between students who utilized and those who did not utilize Google Sites. Therefore, it can be concluded that learning with Google Sites in the topic of value comparison has a significant effect on students' learning achievement.